Editorial - Deniz Evcik, (Archives of Rheumatology, 2010)
It is a great pleasure to introduce you the first issue of the Turkish Journal of Rheumatology in English. Starting from the March 2010 issue, only manuscripts written in English will be accepted for review process and all issues will be published in English. In this inaugural issue of TJR, there are 9 interesting papers and an invited review from Tuulikki Sokka As the present Editorial Board leaves the five years behind, the Journal wishes to improve its standards expecting that the large audience of authors, critics and readers do continue their support in the coming years. The editorial team is already encouraged by both the number of papers being submitted and the quality of research and discussion they encompass. The Turkish League Against Rheumatism, has always been the pioneer association in rheumatology practice in Turkey. This year will host the Fourth Annual Conference of Rheumatology. The conference will be held between 7-11 April 2010 in Antalya. Hereby, I would like to invite you to the congress. Best regards Deniz Evcik, MD Editor